Niacin Inhibits Vascular Inflammation via Downregulating Nuclear Transcription Factor-κB Signaling Pathway - Yanhong Si; Ying Zhang; Jilong Zhao; Shoudong Guo; Lei Zhai; Shutong Yao; Hui Sang; Nana Yang; Guohua Song; Jue Gu; Shucun Qin (Mediators of Inflammation)
The study aimed to investigate the effect of niacin on vascular inflammatory lesions in vivo and in vitro as well as its lipid-regulating mechanism. In vivo study revealed that niacin downregulated the levels of inflammatory factors (IL-6 and TNF-α) in plasma, suppressed protein expression of CD68 and NF-κB p65 in arterial wall, and attenuated oxidative stress in guinea pigs that have been fed high fat diet. In vitro study further confirmed that niacin decreased the secretion of IL-6 and TNF-α and inhibited NF-κB p65 and notch1 protein expression in oxLDL-stimulated HUVECs and THP-1 macrophages. Moreover, niacin attenuated oxLDL-induced apoptosis of HUVECs as well. In addition, niacin significantly lessened lipid deposition in arterial wall, increased HDL-C and apoA levels and decreased TG and non-HDL-C levels in plasma, and upregulated the mRNA amount of cholesterol 7α-hydroxylase A1 in liver of guinea pigs. These data suggest for the first time that niacin inhibits vascular inflammation in vivo and in vitro via downregulating NF-κB signaling pathway. Furthermore, niacin also modulates plasma lipid by upregulating the expression of factors involved in the process of reverse cholesterol transport.